The Crime Prevention Approach in West Bagong Silang Police Sub Station 12 in Bagong Silang Caloocan City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crime is one of today's major universal probleMs. Many lives and property have beendestroyed because of the lawlessness committed. Society views most crimes, such asrobbery, rape, murder, and assault, as deviating and destroying human life and property. Ifyou want more and you want something stronger, take the less powerful plan. Crimeprevention is a crucial aspect of the criminal justice field. Prevention efforts are important forlaw enforcement officials and others associated with eliminating and reducing crime to enforceprecautionary and safety measures in one's Community to reduce the victimization rate. Incrime prevention, there may be a need to initiate and implement myriad effective policies. Itcan be undertaken by the government of the day, individuals, or other security-basedagencies.It helps us to point out different recommendations as we see that based on the data gathered,we conclude that the main problems in approaching crime are the following: Lack of patrollers,especially in crime-prone areas, Lack of funds for maintenance of patrol cars, and motorvehicles and lastly, Lack of communications due to limited issuance of radios. In addition, theresearchers have seen the lack of awareness of the community about the crime preventionprogram, lack of cooperation and efforts on the part of the community members to attend thefree Seminar about the crime prevention program, and Lack of knowledge among communitymembers about how they can help prevent crime and lastly, Lack of communication linesbetween the police and the community together with the barangay officials. Therefore, throughconducting this study, researchers have recommended the following: Raising programawareness about crime prevention encourages community members to attend the freeSeminar by the PNP about the crime prevention program.
Keywords: Criminology